Providing Access to Care through a 24‐Hour Dedicated Stone Line. Issue 1 (January 2017) - Rapp, David E.; Wood, Nada L.; Wright, Jacob A.; Booth, Brigette A.; Colhoun, Andrew; Kramolowsky, Eugene V.
Abstract : Introduction: : Many patients with urolithiasis are seen acutely in the emergency department for initial treatment. In an effort to improve cost and quality of care increasing focus has been placed on shifting management of low acuity conditions from emergency departments to outpatient settings. One barrier to such initiatives is timely access to outpatient services. We established a telephone stone line to provide access to outpatient urological care of kidney stones and we report our initial experience. Methods: : A 24‐hour dedicated telephone stone line was created with calls answered by dedicated staff. A computer program was created to track stone line calls and post‐call care. We retrospectively analyzed all stone line calls received in a 4‐year period with the focus on utilization and cost. An e‐mail survey was performed to assess patient satisfaction. Results: : Between January 2009 and July 2013 the mean call volume was 2, 107 per year. A significant distribution of calls was seen across all days and hours. Duration was less than 15 minutes in 7, 761 calls (82%). Patients or family members placed 77% of calls and physicians placed 16%. As a result of a stone line call, 4, 173 patients (76%) were seen by a urologist within 48 hours. Of the patients 88% reported satisfaction with the stone line. The mean annual cost of providing the telephone stone line was 51, 873. Conclusions: : Our experience demonstrates sustained utilization of and satisfaction with the telephone stone line. Further, stone line use results in timely outpatient evaluation in the majority of patients. Further analysis to assess for a cost benefit is ongoing.